Best Answer

Perhaps, using the Quadratic Equation...

y=x2+5x-6

Solve for x:

x2+5x+(-6-y)=0

Using the Quadratic Equation:

x = .5 *(-5 (+-) (25 + (24+4y)).5) = -2.5 (+-) .5*(49+4y).5

Substitute y for x, x for y:

y = -2.5 (+-) .5*(49+4x).5

Q: Is it possible to find the inverse equation of y equals x squared plus 5x minus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

no

To find the inverse, replace y with x, and x with y. So, the inverse of the equation is: x = 4yWhich is equal to:y = x/4

No, It's a a quadratic equation because you have X squared.

It is a quadratic equation in X.

no, because xx=x squared, and x squared is not linear

Related questions

no

To find the inverse, replace y with x, and x with y. So, the inverse of the equation is: x = 4yWhich is equal to:y = x/4

square root of x/pi

No, It's a a quadratic equation because you have X squared.

It is a quadratic equation in X.

no, because xx=x squared, and x squared is not linear

It is the Cartesian equation of an ellipse.

Yes it is. The thing that makes it a quadratic equation is that "x squared" in there.

It is the equation of a parabola.

It is a quadratic equation in the one variable.

Relativity.

The greatness of 4 squared and 3 squared is expressed by the equation: 16 - 9 which equals 7.3 squared equals 3 x 3 = 94 squared equals 4 x 4 = 1616 - 9 = 7